Técnicas de aprendizaje aplicado a la Hidrodinámica en Sistemas de Riego para la agricultura, dirigido a los estudiantes de la Escuela de Ingeniería Agronómica de la Facultad de Recursos Naturales de la Escuela Superior Politécnica de Chimborazo en el período 2015-2016. - Paredes Godoy, María Magdalena (2016)
To meet the need for alternative methodological tools to improve teaching based on the learning-by-doing approach, we conducted research we call “learning techniques applied to hydrodynamics in agricultural irrigation systems.” The objectives of our research were framed in understanding the concepts, laws and mathematical expressions of hydrodynamics. We compared three techniques: direct experience with functioning irrigation systems, laboratory experimentation based on practical exercises, and problem-solving for real irrigation systems based on appropriately scaled models. Using a quasi-experimental design involving 26 randomly selected, second-semester students in the Agronomy School at ESPOCH, we determined how these techniques influenced learning in hydrodynamics with assessment instruments developed for each activity. We first employed learning tools for each of the three techniques in the usual manner, then we applied them after explanation of each technique. In the first case, we conducted field trips to observe open-tank, sleeved irrigation systems in one of the agricultural properties belonging to ESPOCH and to observe the inverted-siphon system in the community of Chismaute-Telán. For the second technique, we had students calculate density and flow in the irrigation laboratory at ESPOCH. For the third approach, models were presented to students for their practical exercises. It was concluded by Wilcoxon test that all three techniques improved the quality of learning by the students, but that the most influential was direct experience during the field trips, with an average of score of 7.96. The problem-solving exercises followed with a score of 7.06, and last was laboratory experimentation with a score of 6.92. We conclude that the student learns best by “real-world” contact, allowing application of what is taught in the classroom. We recommend using a combination of models and field data for each of the topics, and we encourage teachers to continue reviewing techniques that allow them to reach the student in the best way and foster in them a love for physics.